Genome deletions to overcome the directed loss of gene function in Leishmania - Alpizar-Sosa, Edubiel A.; Kumordzi, Yasmine; Wei, Wenbin; Whitfield, Phillip D.; Barrett, Michael P.; Denny, Paul W. (Frontiers in Cellular and Infection Microbiology, 2022)
With the global reach of the Neglected Tropical Disease leishmaniasis increasing, coupled with a tiny armory of therapeutics which all have problems with resistance, cost, toxicity and/or administration, the validation of new drug targets in the causative insect vector borne protozoa Leishmania spp is more important than ever. Before the introduction of CRISPR Cas9 technology in 2015 genetic validation of new targets was carried out largely by targeted gene knockout through homologous recombination, with the majority of genes targeted (~70%) deemed non-essential. In this study we exploit the ready availability of whole genome sequencing technology to reanalyze one of these historic cell lines, a L. major knockout in the catalytic subunit of serine palmitoyltransferase (LCB2), which causes a complete loss of sphingolipid biosynthesis but remains viable and infective. This revealed a number of Single Nucleotide Polymorphisms, but also the complete loss of several coding regions including a gene encoding a putative ABC3A orthologue, a putative sterol transporter. Hypothesizing that the loss of such a transporter may have facilitated the directed knockout of the catalytic subunit of LCB2 and the complete loss of de novo sphingolipid biosynthesis, we re-examined LCB2 in a L. mexicana line engineered for straightforward CRISPR Cas9 directed manipulation. Strikingly, LCB2 could not be knocked out indicating essentiality. However, simultaneous deletion of LCB2 and the putative ABC3A was possible. This indicated that the loss of the putative ABC3A facilitated the loss of sphingolipid biosynthesis in Leishmania, and suggested that we should re-examine the many other Leishmania knockout lines where genes were deemed non-essential.